Vaccination Reduces Fecal Shedding and Improves Carcass Quality in Pigs with Subclinical Lawsonia intracellularis Infections - Rubén Del Pozo Sacristán; Hanny Swam; Stephan von Berg; Amy Elizabeth Taylor (Vaccines, 2025)
Background/Objectives: Lawsonia intracellularis is a bacterium that causes Proliferative Enteropathy, an enteric infection characterized mainly by diarrhea and growth retardation, leading to important economic losses. Acute and chronic infections are easily diagnosed, and their control by vaccination has been proven efficacious. However, subclinical infections, despite being very prevalent, often remain underdiagnosed and uncontrolled in practice. Scarce research is available on the control of subclinical infections by vaccination, and the benefit in these scenarios remains to be elucidated. Two field trials were carried out to (1) determine the association between the growth and fecal shedding of L. intracellularis in unvaccinated and intramuscularly vaccinated pigs in a farm with subclinical infection and (2) assess the impact of intradermal vaccination against L. intracellularis on clinical performance and carcass quality in a herd with subclinical infection. Methods: A pig herd with subclinical infection was selected. Pigs were vaccinated intramuscularly (study 1) or intradermally (study 2) at weaning. Fecal shedding, performance, clinical parameters, and carcass quality were investigated. Results: Growth was negatively associated with the fecal load of L. intracellularis in non-vaccinated pigs, whereas in vaccinated pigs, growth performance was not impacted by fecal load (study 1). Vaccinated pigs presented a significantly lower fecal load, lower prevalence of tail biting (31.7%) compared with controls (54.2%), less back fat, and a greater Lean Meat percentage (study 2). Conclusions: Vaccination against L. intracellularis in a herd with subclinical infection and low fecal bacterial shedding led to a reduction in fecal shedding, a lower prevalence of tail biting, and an improvement in carcass quality.